The draft genomes of five agriculturally important African orphan crops. Issue 3 (7th December 2018) - Chang, Yue; Liu, Huan; Liu, Min; Liao, Xuezhu; Sahu, Sunil Kumar; Fu, Yuan; Song, Bo; Cheng, Shifeng; Kariba, Robert; Muthemba, Samuel; Hendre, Prasad S; Mayes, Sean; et al.
Abstract: Background: The expanding world population is expected to double the worldwide demand for food by 2050. Eighty-eight percent of countries currently face a serious burden of malnutrition, especially in Africa and south and southeast Asia. About 95% of the food energy needs of humans are fulfilled by just 30 species, of which wheat, maize, and rice provide the majority of calories. Therefore, to diversify and stabilize the global food supply, enhance agricultural productivity, and tackle malnutrition, greater use of neglected or underutilized local plants (so-called orphan crops, but also including a few plants of special significance to agriculture, agroforestry, and nutrition) could be a partial solution. Results: Here, we present draft genome information for five agriculturally, biologically, medicinally, and economically important underutilized plants native to Africa: Vigna subterranea, Lablab purpureus, Faidherbia albida, Sclerocarya birrea, and Moringa oleifera . Assembled genomes range in size from 217 to 654 Mb. In V. subterranea, L. purpureus, F. albida, S. birrea, and M. oleifera, we have predicted 31, 707, 20, 946, 28, 979, 18, 937, and 18, 451 protein-coding genes, respectively. By further analyzing the expansion and contraction of selected gene families, we have characterized root nodule symbiosis genes, transcription factors, and starch biosynthesis-related genes in these genomes. Conclusions: These genome data will be useful to identify and characterize agronomically important genes and understand their modes of action, enabling genomics-based, evolutionary studies, and breeding strategies to design faster, more focused, and predictable crop improvement programs.